Pancreatic surgery - Fingerhut, Abe; Uranues, Selman (Translational Gastroenterology and Hepatology, 2018)
The first documented operation on the pancreas, a distal pancreatectomy with splenectomy for removal of a tumor, was performed in 1882 by Friedrich Trendelenburg (1). The first reported attempt at a pancreatoduodenectomy was performed in 1898 by the Italian surgeon Alessandro Codivilla for a tumor involving the head of the pancreas (2), but the patient did not survive the postoperative period.